Melting of Partially Fluorinated Graphene: From Detachment of Fluorine Atoms to Large Defects and Random Coils - Singh, Sandeep Kumar (2014)
The melting of fluorographene is very unusual and depends strongly on the degree of fluorination. For temperatures below 1000 K, fully fluorinated graphene (FFG) is thermo-mechanically more stable than graphene but at T m ≈ 2800 K FFG transits to random coils which is almost twice lower than the melting temperature of graphene, i.e. 5300 K. For fluorinated graphene (PFG) up to 30% ripples causes detachment of individual F-atoms around 2000 K while for 40-60% fluorination, large defects are formed beyond 1500 K and beyond 60% of fluorination F-atoms remain bonded to graphene until melting. The results agree with recent experiments on the dependence of the reversibility of the fluorination process on the percentage of fluorination.